Improved maximum power point tracking algorithm with cuk converter for PV systems. Issue 13 (19th January 2018) - Sun, Zongchang; Yang, Zhoujun
Abstract : The maximum power point tracking (MPPT) techniques are essential for the optimisation of the efficiency in the photovoltaic (PV) systems. Here, a practical PV model is discussed and employed, and cuk converter is selected as MPPT's DC–DC converter for PV systems. Then, on the basis of the power–current ( P – I ) characteristics curve of a PV cell, an improved MPPT algorithm with direct control by using the fuzzy controller is proposed. Compared with some algorithms mentioned here, the proposed algorithm is able to track a more accurate MPP quickly and have a smaller steady‐state oscillation. To validate its correctness and good performance under the varying environmental conditions, simulation study on it is carried out in MATLAB/Simulink. Also, simulation results demonstrate the proposed algorithm here is feasible and in contrast, it has a faster dynamic and more robust steady‐state performance.